A novel truss formwork made from Casuarina wood - Hussein, Moustafa (AUC Knowledge Fountain, 2020)
Wood is classified as one of the most common building materials due to its diverse nature. In Egypt, most of the wood used in different industries are imported from several places such as North America and Australia. Nowadays, Casuarina is considered one of the fast-growing trees in relatively arid countries like Egypt. The thesis aims to test the mechanical properties for the most two common species of Casuarina in Egypt, which are “Glauca” and “Cunninghamiana”. The thesis focused on testing both species for compression parallel to the grain, compression perpendicular to the grain, static bending tests while the tension parallel to the grain, tension perpendicular to the grain and cleavage tests were only tested on Glauca because Cunninghamiana was excluded after the first three tests due to the high variability in its results. The results of the mechanical tests showed that Casuarina Glauca was promising because it has the sufficient strength that could enable it to be used in construction applications. A secondary scope in this thesis is to investigate the moisture content effect on the mechanical properties of both Casuarina species through testing both Casuarina species in three different moisture contents. Similar to the most types of wood reducing the moisture content improved the strength and the modulus of elasticity for all the mechanical tests. The thesis also aims to design, manufacture and test a formwork truss made of Casuarina Glauca. Three trusses made of Casuarina Glauca were manufactured and tested under bending as structural application for a formwork beam and the results were promising and may achieve structural and economic gain for the wood industry in Egypt. A cost study comparing the Casuarina Glauca truss to the GT 24 truss produced by PERI company. The comparison was done by applying both trusses on a slab and calculating the number of units, the total weight and the total cost of each system. The results of the cost study have proven that the designed Casuarina truss to be a cost effective when compared to the GT 24 PERI formwork system.